1993
DOI: 10.1021/ja00055a052
|View full text |Cite
|
Sign up to set email alerts
|

Structure and photoelectron spectrum of 3,3'-bicyclopropenyl

Abstract: The X-ray crystal structure of thermally sensitive 3,3'-bicyclopropenyl (mp 198 K) has been determined at 103 K using a miniature-zone melting procedure with focused infrared light. The structural parameters calculated for the anti conformer using the Hartree-Fock self-consistent field procedure with a 3-21 G basis set compare well with the experimental data. The photoelectron spectrum of 1, which exhibits three peaks of different heights well separated from a smaller fourth one, can be interpreted in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…3,3-Bicyclopropenyl ( 70 ) is probably the least stable of the known four valence isomers of benzene . It was prepared by Billups and Haley in 1989, and its structure in the crystalline state was determined by X-ray analysis . In the same paper, its electronic structure was investigated by PE spectroscopy and quantum chemical computations.…”
Section: 51 Compounds With Two Three-membered Rings and Small Polycyc...mentioning
confidence: 99%
“…3,3-Bicyclopropenyl ( 70 ) is probably the least stable of the known four valence isomers of benzene . It was prepared by Billups and Haley in 1989, and its structure in the crystalline state was determined by X-ray analysis . In the same paper, its electronic structure was investigated by PE spectroscopy and quantum chemical computations.…”
Section: 51 Compounds With Two Three-membered Rings and Small Polycyc...mentioning
confidence: 99%
“…The bicyclopropenyl hydrocarbon (CH) 6 8 is known to have the trans C 2h structure, 18 and indeed, the N6 analog has a minimum energy in this same conformation. One can imagine this structure as having lone pairs of electrons trans to each other at either end of the central N-N bond.…”
Section: Calculationsmentioning
confidence: 99%
“…In addition to the valence isomers of benzene, several other isomers, both cyclic and acyclic, exist and are interesting in their own right. Exploration of the structural limitations in organic chemistry is an inspiring and challenging arena, which warrants a judicious combination of experiment and theory. Several experimental studies have been reported on the rearrangements of acyclic isomers of C 6 H 6 in generating other acyclic and cyclic isomeric structures. Prominently, the rearrangement of 1,5-hexadiyne to other isomeric forms of C 6 H 6 has been the interest for more than three decades. , Huntsman and Wristers have synthesized 3,4-dimethylenecyclobutene, a monocyclic isomer, in high yield from 1,5-hexadiyne by thermal cyclization at 350 °C, which was reported to occur via 1,2,4,5-hexatetraene .…”
Section: Introductionmentioning
confidence: 99%